The Influence of Employee Performance on Customer Satisfaction at Ramayana Bali Mall Diponegoro - Sari, Desak Made Indah Paramitha; Fatmayoni, I Gusti Agung Ayu Intan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Ramayana Bali Mall is a retail company located on Jln. Diponegoro No. 103 West Denpasar. Being in this era of sophisticated technology has made many people take the initiative to do retail business both online and offline. This shows that there is very tight competition. Therefore, Ramayana Bali Mall improves employee performance, one aspect of which is good service and providing comfortable facilities to customers. In this research, the researcher used a survey method and collected data using a questionnaire and made it in the form of a statement. The research subjects in this study were Ramayana Bali Mall customers who visited the shop directly. The author's aim in conducting this research is to find out how employees perform and their influence on customer satisfaction at Ramayana Bali Mall. Based on the research results, it can be concluded that the influence of employee performance has a very positive and significant effect on customer satisfaction. This shows that the better the performance of Ramayana Bali Mall employees, the more customer satisfaction will increase.